2008
DOI: 10.1002/hrm.20211
|View full text |Cite
|
Sign up to set email alerts
|

Overlooked and underutilized: People with disabilities are an untapped human resource

Abstract: The retirement of baby boomers along with a smaller cohort group of young people replacing them poses a challenge for employers in the future—where will they find the workers they need? One largely untapped source of human resources is people with disabilities (PWDs). Why have employers mostly ignored this large labor pool? This research used a semistructured interview approach with 38 executives across a broad array of industries and geographic regions to examine why employers don't hire PWDs and what they be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
186
2
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 216 publications
(216 citation statements)
references
References 29 publications
(23 reference statements)
7
186
2
11
Order By: Relevance
“…[2][3] From the employers perspective it has been shown that LMP of persons with disabilities has positive effects on the total workforce of an organisation, for example, the decreased absence and fluctuation rates. 4 The society as a whole also benefits in terms of fewer disability pensions, higher tax revenue and more labour force diversity. 3 The LMP in the international SCI population varies between 3 and 80%, in part because of inconsistent definitions of work and inconsistent study methods.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3] From the employers perspective it has been shown that LMP of persons with disabilities has positive effects on the total workforce of an organisation, for example, the decreased absence and fluctuation rates. 4 The society as a whole also benefits in terms of fewer disability pensions, higher tax revenue and more labour force diversity. 3 The LMP in the international SCI population varies between 3 and 80%, in part because of inconsistent definitions of work and inconsistent study methods.…”
Section: Introductionmentioning
confidence: 99%
“…Though some studies discuss the relationship between the presence of PwD and performance, their focus is usually on individual or group performance, such as in Baumgartner, Bohm and Dwertmann (2014). Though other researchers have shown interest in understanding how a greater presence of PwD occurs at the organizational level, these are mostly conceptual and theoretical studies that ponder factors that influence how PwD are treated within the organizational environment (Stone & Colella, 1996), obstacles faced by these individuals (Kulkarni & Lengnick-Hall, 2013), and possible personnel management strategies for managing PwD within organizations (Lengnick-Hall, Gaunt & Kulkarni, 2008). As a whole, these studies show how the presence of PwD in firms is marked by prejudice, stigma and even repulsion, largely generating the perception that a higher proportion of PwD in firms generates a negative impact.…”
Section: The Relationship Between Productivity and Proportion Of Peopmentioning
confidence: 99%
“…Por um lado, à semelhança do que acontece na população em geral, a escolaridade e a idade constituem fatores importantes nesse acesso; por outro, aliam-se aos fatores referidos variáveis inerentes à deficiência visual, como a autonomia no cotidiano e adesigualdade de oportunidades de trabalho dos candidatos (ACAPO, 2012;Costa, 2012). A falta de informação, a qual origina atitudes preconceituosas por parte dos possíveis empregadores (Markel & Barclay, 2009;Vieira & Vieira, 2015) tem sido também indicada pela investigação (Kaye, Stephen, Lita, & Jones, 2011;Kulkarni & Lengnick-Hall, 2014;Lengnick-Hall, Gaunt, & Kulkarni, 2008) como um dos principais fatores que limitam o acesso ao emprego por parte dessa população.…”
unclassified
“…Quando surge um indivíduo com deficiência em um processo de seleção, a recomendação é que seja realçado o perfil apresentado pelo candidato em termos de suas competências, habilidades, conhecimentos e experiência para desempenhar as funções (Costa, 2012;Lengnick-Hall et al, 2008), aliás, procedimentos que também devem ocorrer com candidatos sem deficiência. A legislação portuguesa reforça essa preocupação, referindo o Código do Trabalho (Lei 7/2009 de 12 de Fevereiro), no artigo 24º, ponto 1, que O trabalhador ou candidato a emprego tem direito a igualdade de oportunidades e de tratamento no que se refere ao acesso ao emprego (…) não podendo ser privilegiado, beneficiado, prejudicado, privado de qualquer direito ou isento dequalquer dever em razão, nomeadamente, de (…) deficiência (…).…”
unclassified
See 1 more Smart Citation